DEVELOPMENT AND QUALITY ASSESSMENT OF APPLE (MALUS PUMILA VAR. DOMESTICA) AND PINEAPPLE (ANANAS COMOSUS L. VAR. QUEEN) FLAVORED KOMBUCHA - Cullano, Reciel Ann T; Tiu, Ann Myril C (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
A response surface methodology (RSM) was used for the determination of the best point combination of apple ( Malus domestica ) and pineapple ( Ananas comosus ) pulp to produce an acceptable fermented tea (kombucha) beverage. This study specifically aims to develop kombucha with tropical flavors to improve its sensory acceptability and physico-chemical properties. Kombucha was produced using black oolong leaves and fermented for eight (8) days. Apple and pineapple pulp were added in 3%, 6%, and 9% w/v each arranged in a Central Composite Design (CCD) with a quadratic model. Sensory acceptability attributes that were determined are color, appearance, aroma, sourness, sweetness, mouthfeel, and general acceptability. Physico-chemical tests include pH total soluble solids (TSS), titratable acidity (TA) and L*, a*, and b* color values. The effects of the sensory and physico-chemical parameters were studied by employing a second-order central composite design. The coefficient of determination, R 2 for sensory analysis, ranged from 0.5- 0.7 and 0.72- 0.98 for the physico-chemical tests. Analysis of the regression coefficients showed that the different levels of apple and pineapple pulp did not affect the sensory acceptability of kombucha. However, pineapple levels significantly affected the TA, L* & a* values as they exerted a highly significant influence (p < 0.001) on these parameters. Based on the contour plots overlay, best formulation levels for the fruits are 7.3% apple pulp and 9.2% pineapple pulp.